2022
DOI: 10.3390/agriculture12081264
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Tillage and Fertilization Patterns to Improve Soil Physical Properties, NUE and Economic Benefits of Wheat-Maize Crop Rotation Systems

Abstract: Winter wheat and summer maize rotation is the main cropping pattern in the North China Plain (NCP). There are still problems with farmers’ production modes, including shallow tillage layers, single application of chemical fertilizer causing plow bottom layer thickening and soil pH decrease. A two-factor location experiment was conducted to investigate the effects of different tillage and fertilization patterns on the soil physical properties, soil organic carbon (SOC), nitrogen-use efficiency, and crop yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Guo et al 27 showed that the long-term application of organic fertilizer significantly increased soil water storage, and the increase rate was positively correlated with the application amount and time. Zhang et al 28 found that combining organic fertilizer with inorganic fertilizer reduced evaporation and increased the soil water content. On the other hand, some studies showed that improvements in maize yield varied regionally.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al 27 showed that the long-term application of organic fertilizer significantly increased soil water storage, and the increase rate was positively correlated with the application amount and time. Zhang et al 28 found that combining organic fertilizer with inorganic fertilizer reduced evaporation and increased the soil water content. On the other hand, some studies showed that improvements in maize yield varied regionally.…”
Section: Introductionmentioning
confidence: 99%